Kingdom of the Netherlands-Netherlands Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper for the Netherlands highlights that Dutch cost competitiveness deteriorated significantly in the years prior to 2004. The relatively poor economic performance during the new millennium contributed to these concerns generally, as did restrained export performance more specifically. The deceleration of private consumption growth started earlier than the deceleration of per capita real disposable income growth, and occurred at a time when the unemployment rate has been at a historic low and interest rates had declined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet